Randbemærkninger til Kurt Weills radiokantate Berliner Requiem - Krabbe, Niels (Danish Yearbook of Musicology, 2000)
The article deals with scattered aspects of Weill’s and Brecht’s Berliner Requiem. The work is seen as an example of the questioning of the traditional concept of the work of art, inherited from the 19th century, and as a work born by the possibilities and the aesthetics of the new broadcasting medium, the latter being discussed at a certain length on the basis of the leading music periodicals of the late 1920s. The origins of Brecht’s texts are traced, and a few musical characteristics of the work are pointed at.